2017
DOI: 10.1155/2017/9640108
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Therapeutics for Heart Failure: Focus on Mesenchymal Stem Cells

Abstract: Resulting from a various etiologies, the most notable remains ischemia; heart failure (HF) manifests as the common end pathway of many cardiovascular processes and remains among the top causes for hospitalization and a major cause of morbidity and mortality worldwide. Current pharmacologic treatment for HF utilizes pharmacologic agents to control symptoms and slow further deterioration; however, on a cellular level, in a patient with progressive disease, fibrosis and cardiac remodeling can continue leading to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 88 publications
0
14
0
Order By: Relevance
“…In addition to the cells of mesodermal origin (osteoblasts, chondroblasts, and adipocytes), MSCs are capable of generating neural cells, hepatocytes, alveolar epithelial cells, insulinproducing cells, cardiomyocytes, indicating their clinical application (7)(8)(9)(10)(11)(12)(13)(14). Several lines of evidence suggested that MSCs have capacity to differentiate into functional cardiomyocytes (9), hepatocytes (10,11), alveolar epithelial cells and lung precursor cells (13) contributing to the regeneration of injured myocardium, liver and lungs (12,(15)(16)(17). Additionally, in paracrine manner, through the production of immunomodulatory factors (indoleamine 2,3-dioxygenase (IDO), prostaglandin E2 (PGE2), nitric oxide (NO), transforming growth factor beta (TGF-β), interleukin (IL)-10, interleukin 1 receptor antagonist (IL-1Ra) and growth related oncogene (GRO), MSCs are able to suppress detrimental autoimmune response and to attenuate autoimmune and chronic, inflammatory diseases (3,18,19).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the cells of mesodermal origin (osteoblasts, chondroblasts, and adipocytes), MSCs are capable of generating neural cells, hepatocytes, alveolar epithelial cells, insulinproducing cells, cardiomyocytes, indicating their clinical application (7)(8)(9)(10)(11)(12)(13)(14). Several lines of evidence suggested that MSCs have capacity to differentiate into functional cardiomyocytes (9), hepatocytes (10,11), alveolar epithelial cells and lung precursor cells (13) contributing to the regeneration of injured myocardium, liver and lungs (12,(15)(16)(17). Additionally, in paracrine manner, through the production of immunomodulatory factors (indoleamine 2,3-dioxygenase (IDO), prostaglandin E2 (PGE2), nitric oxide (NO), transforming growth factor beta (TGF-β), interleukin (IL)-10, interleukin 1 receptor antagonist (IL-1Ra) and growth related oncogene (GRO), MSCs are able to suppress detrimental autoimmune response and to attenuate autoimmune and chronic, inflammatory diseases (3,18,19).…”
Section: Introductionmentioning
confidence: 99%
“…The main cells used for stem cell therapy for cardiac regeneration are MSCs, cardiac progenitor cells, and differentiated endothelial cells 17 19 . In clinical studies of ischemic heart disease, improvement was shown in the left ventricular ejection fraction in only 8 of 22 trials, and this analysis concluded that adult stem cell therapy was not ready for routine clinical application 20 .…”
Section: Discussionmentioning
confidence: 99%
“…The expression of cardiomyogenic differentiation markers cTNT, βMHC and ASA by 5-aza treated cells was analyzed by fluorescent immunocytochemistry. Quantitative analysis of immunoflorescent images revealed that as compared to BM-MSC, AF-MSC had significantly higher expression of cTNT (5.0×10 4 ±0.6×10 4 4 ; p<0.05) (Fig. 4).…”
Section: Expression Of Cardiomyogenic Markers By Af-msc and Bm-msc;mentioning
confidence: 99%
“…MSC can also be obtained from fetal tissues such as amniotic fluid, umbilical cord blood and Wharton's jelly (3). Of these, the bone marrow (BM) derived MSC (BM-MSC) have been most commonly studied for myocardial regeneration in several pre-clinical and clinical studies but the therapeutic outcome has been variable, which may be because of their limited cardiomyogenic potential (4)(5)(6). The collection of MSC from BM entails an invasive procedure and it is difficult to get MSC from healthy individuals.…”
Section: Introductionmentioning
confidence: 99%